Teaching English Components To Young Learners - Kurniasih, Siwi Karmadi (English Education Department, Universitas Islam Indonesia, 2008)
Teaching English for children requires thoughtful considerations of what and how to teach. It needs full considerations such as what components of the language should be taught, what method should be applied, and what teaching technique should be employed.Teaching English components i.e. grammar, vocabulary, and pronunciation, a teacher must take the nature of children learning into account. Teaching vocabulary, teacher should plan and organize the material to learn carefully. Concrete objects should come before the abstract ones. Teaching vocabulary is not only about teaching words as separate units but formulaic chunks. In addition, teaching strategies play an important role in children's learning success.Learning grammar is closely related to learning vocabulary. When children learn vocabulary through learning formulaic chunks, the teacher can discuss the grammar too. One important thing that teacher should bear in her mind is that the opportunity to use the language in a meaning-focused situation is as important as learning the grammatical patterns.The other language component to learn is pronunciation. As the other components, teaching pronunciation to young learners also need thoughtful consideration. Normally native speakers say an expression in blended sounds. They will not say each word clearly as separate unit. Hence, teachers should drill students to say expressions and guide students to feel and experience saying them in normal and natural way.